STRESS MANAGEMENT EFFECTIVENESS AT SATHABISHAA ENGINEERING INDUSTRIES PVT LTD COMPANY IN CHENNAI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Stress Management has become a most important and valuable technique to boost theemployee morale and the company’s productivity in all companies. All the Organizations haveunderstood that the employees play a key role and they should be out of stress to give a highperformance atmosphere. There are varieties of techniques to manage stress in organizations.High stress jobs refer to work, which involves hectic schedule and complex job responsibilitiesthat result into imbalance between personal and work life. Overwork may affect physical healthof individual resulting into ineffective work and dissatisfaction-among employees leading toimbalance in family or personal life also. Due to improper job role assignment, improperworking conditions, underutilization of skills and organizational politics the employees could bestressed. There are lots of individualstress like role ambiguity, psychological hardiness, and typeof personality that affect the morale of the employees as a whole.